Perkembangan Sosial Emosional Anak Usia Dini Dalam Penggunaan Gadget - Juraidah Juraidah; Nayla Rizka Irwani; Nurhayati Nurhayati; Rapiqah Hayati; Yasmina Fajri; Hairani Ananda Putri6; Khadijah Khadijah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Currently, technological advancements are progressing rapidly, and various modern inventions are aimed at enchancing human mobility and freedom of movement in daily life. One example of rapidy developing technology is gadgets. This journal aims to understand the impact of gadgets in the socio-emotional development of young children. The authors of this journal employed a literature review research method. The use of gadgets in early childhood has a significant impact on their socio-emotional deveploment, both positive and negative, depending on the duration, content, and contet of usage